The Multifaceted Impact of COVID-19: Health, Emotions, Well-Being, and Risk Assessment. (December 2021) - Robinson, Laura; Huang, Kuo-Ting; Schulz, Jeremy; Chiaraluce, Cara; Khilnani, Aneka; Johnston, Elisha
Analyzing diverse and rich data on the COVID-19 pandemic, this issue of the American Behavioral Scientist offers important insights into health and risk assessment in a time of unprecedented crisis in the 21st century. This issue explores health, emotions, and well-being vis-à-vis the pandemic and its societal impacts. Across the articles, we see the complex ways that this global health crisis has consequences for individuals and groups as they engage in risk assessment and grapple with the secondary effects of the pandemic. Within this issue, we observe the importance of information exchange, networks and relationships, emotional and economic well-being, and risk perception. All of these phenomena converge in the myriad ways that the COVID-19 pandemic forces people to reevaluate everyday activities in consequential life realms. As the issue as a whole illuminates, human emotions and risk assessment are powerful forces that prompt practices and behaviors even in a time of public health crisis.